Sistem Informasi Publik Sekretariat DPRD Kabupaten Malinau - Henri Tetiawadi Henri; Lumadi Lumadi (Jurnal Bangkit Indonesia, 2023)
The Secretariat of the Regional People's Representative Council (DPRD) is a public organization in which there are various kinds of interests, both organizational interests, community interests and individual interests which must be fulfilled immediately. In relation to these interests, it is necessary to pay close attention to the DPRD Secretariat in the system for managing and presenting information that is accurate, relevant and timely to the public. In providing information services to the public, the DPRD Secretariat still has several problems, even though it is currently using computer technology. However, the computer that is used only functions to store information data whose nature cannot be accessed directly by the public. Apart from that, in conveying information about the activities of the council and the activities of the DPRD Secretariat, it is still conventional and the way to publish it is through third parties, because the DPRD Secretariat of Malinau Regency does not yet have proper media and does not yet have an application that can manage an online public information system. The website is one of the internet-based information media that is able to meet these information needs. Information about business and business is widely available on the internet and can be used by anyone free of charge. In addition, the website can also be used as a media for advertising, transactions and delivery of information by companies or organizations, both business and non-business. The information provided can be in the form of promotion of a product, public services, existence of an agency and so on. Researchers conducted research related to public information systems at the DPRD Secretariat of Malinau Regency and provided application design proposals that were compiled into an information system for public services